2021
DOI: 10.53048/johass.977133
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0 Aracı ile Desteklenen Çevrim İçi Fen Bilimleri Öğretimi: Sanal Müze Etkinliği

Abstract: In this study, it is aimed to investigate the effect of the online science course, which is carried out by using the virtual museums created with the web 2.0 tool, on the academic achievement and science attitudes of the fifth-grade students. In addition, student opinions about the virtual museum were also taken within the scope of the study. The research was conducted based on mixed method research in which qualitative and quantitative research models were combined. Quasi-experimental design with pre-test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Other results of the study showed that the PSCTs agreed that integrating Web 2.0 tools in the classroom would encourage active involvement and make learning more enjoyable. Similarly, it was revealed in the studies that students found science courses conducted by the usage of Web 2.0 tools to be more enjoyable (Arslan & Arı, 2021;Karadağ & Garip, 2021;Weller, 2013). Moreover, Punie and Cabrera (2006) stated that students who continuously utilize different Web 2.0 tools during their learning process will remain more active and enthusiastic in this process.…”
Section: Discussionmentioning
confidence: 96%
“…Other results of the study showed that the PSCTs agreed that integrating Web 2.0 tools in the classroom would encourage active involvement and make learning more enjoyable. Similarly, it was revealed in the studies that students found science courses conducted by the usage of Web 2.0 tools to be more enjoyable (Arslan & Arı, 2021;Karadağ & Garip, 2021;Weller, 2013). Moreover, Punie and Cabrera (2006) stated that students who continuously utilize different Web 2.0 tools during their learning process will remain more active and enthusiastic in this process.…”
Section: Discussionmentioning
confidence: 96%
“…Artsteps is an online platform that can organize virtual and interactive exhibitions in a web-based environment, allowing showcased works to be viewed by others using Internet access (Dumitrescu et al, 2014). Virtual exhibitions can be defined as web-based online collections of hypermedia or multi-dimensional information that is captured or dynamically rendered and grouped into specific themes, concepts, topics, or ideas (Almurbati, 2021;Arslan & Ari, 2021;Ade et al, 2023). The Artsteps technology facilitates users in creating three-dimensional virtual exhibition spaces for both interior and exterior environments, and it can provide a more realistic impression with Virtual Reality (VR).…”
Section: Introductionmentioning
confidence: 99%